Pentraxin-3 Level Assessment Among Ischemic Stroke Patients with Polycystic Ovarian Syndrome - Mufeed Akram Taha; Sahar A. Taha; Esraa Abdulkareem Mohammed (Diyala Journal of Medicine, 2025)
Background: Pentraxin-3 (PTX3) is an important component of the innate immune system, playing a significant role in the inflammatory process and tissue damage. Assessing its levels in different clinical conditions may offer insights into its diagnostic and prognostic significance. Objectives: This study aims to evaluate whether PTX3 levels are elevated in ischemic stroke patients with PCOS and whether increased PTX3 is linked to greater stroke risk and worse outcomes. Patients and Methods: A case-control study was conducted in the neurology and obstetrics & gynecology clinics at Azadi Teaching Hospital in Kirkuk starting from 1st February 2023 to 1st March 2024. Women diagnosed with polycystic ovarian syndrome (PCOS) according to Rotterdam criteria were divided into three groups: the first group had PCOS with stroke, while the second group had PCOS without stroke; and the third group was considered an age matching control group with age ranges between 18 and 50 years. Blood samples were withdrawn in the morning to determine the levels of PTX3, C-reactive protein (CRP), triglyceride/ high density lipoprotein (TG/HDL) ratio, and homeostatic model assessment for insulin resistance (HOMA-IR) and measured in all studied groups. Results: The level of PTX3 was significantly higher in patients with PCOS with stroke group (5.717 ± 1.172 ng/mL) than those without Stroke (3.665 ± 1.085 ng/mL) and Control (2.377 ± 0.740 ng/mL) groups (p < 0.001). Pentraxin3 levels positively correlated with stroke severity (r = 0.42, p < 0.001), while there was no significant correlation with CRP, TG/HDL Ratio, and HOMA-IR. Conclusion: Pentraxin-3 levels are markedly higher in PCOS patients who have had an ischemic stroke, and the level is in proportion to the severity of the stroke. This means that PTX3 could potentially be used as a biomarker for risk assessment. Keywords: Polycystic ovarian syndrome; Ischemic stroke; Pentraxin 3, CRP, PCOS